Financial and Managerial Accounting - Warren, Carl S., author; Reeve, James M., 1953-, author; Duchac, Jonathan E., author (Boston, MA : Cengage Learning, 2018)
1. Introduction to Accounting and Business.2. Analyzing Transactions.3. The Adjusting Process.4. Completing the Accounting Cycle.5. Accounting for Merchandising Businesses.6. Inventories.7. Internal Control and Cash.8. Receivables.9. Long-Term Assets: Fixed and Intangible.10. Liabilities: Current, Installment Notes, and Contingencies11. Liabilities: Bonds Payable.12. Corporations: Organization, Stock Transactions, and Dividends.13. Statement of Cash Flows.14. Financial Statement Analysis.15. Introduction to Managerial Accounting.16. Job Order Costing.17. Process Costing Systems.18. Activity-Based Costing.19. Cost-Volume-Profit Analysis.20. Variable Costing for Management Analysis.21. Budgeting.22. Evaluating Variances from Standard Costs.23. Evaluating Decentralized Operations.24. Differential Analysis and Product Pricing.25. Capital Investment Analysis.26. Lean Manufacturing and Activity Analysis.Appendix A: Interest Tables.Appendix B: Revenue Recognition Appendix C: International Financial Reporting Standards.Appendix D: Investments.Appendix E: Nike Inc., Form 10-K for the Fiscal Year Ended May 31, 2015.Glossary. Index